Penguatan Pengetahuan tentang Komposisi dan Tekstur MP ASI bagi Ibu - Hasanah, Uswatun; Antari, Gladeva Yugi (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Malnutrition issues in infants, particularly related to complementary feeding (MP ASI), remain a challenge in many areas, including Pringgarata, Central Lombok Regency. Maternal knowledge about the composition and texture of MP ASI suitable for a baby’s age is crucial to prevent nutritional problems such as stunting and malnutrition. This community service aims to enhance maternal knowledge regarding the composition and texture of MP ASI through interactive training. The method used is a qualitative approach with a participatory design, involving 20 mothers with infants under 12 months old in the Pringgarata area. Activities included education using leaflets, demonstrations on preparing MP ASI, and group discussions. Evaluation was carried out using pre-test and post-test questionnaires, interviews, and direct observation of changes in MP ASI feeding behavior. Results showed a 25% increase in maternal knowledge after the training, along with positive behavioral changes in providing MP ASI according to the baby’s age. In conclusion, community-based training can effectively improve maternal knowledge and skills in providing age-appropriate MP ASI, thereby reducing the risk of malnutrition in infants in areas with limited health information access.